2006
DOI: 10.1021/bm060186f
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Aggregation of Conjugates of Streptavidin with Smart Block Copolymers Prepared via the RAFT Copolymerization Technique

Abstract: Block copolymers containing stimuli-responsive segments provide important new opportunities for controlling the activity and aggregation properties of protein-polymer conjugates. We have prepared a RAFT block copolymer of a biotin-terminated poly(N-isopropylacrylamide) (PNIPAAm)-b-poly(acrylic acid) (PAA). The number-average molecular weight (M(n)) of the (PNIPAAm)-b-(PAA) copolymer was determined to be 17.4 kDa (M(w)/M(n) = 1.09). The PNIPAAm block had an M(n) of 9.5 kDa and the poly(acrylic acid) (PAA) block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 22 publications
0
116
0
Order By: Relevance
“…249 [408] MA [405] St [407] St [408] 250* [405] S S N N N S S 251 [404] MA [405] St [407,409] MA [405] St [404] 252* N N N S S 253 [283] S S N N St [409] 374 [410] MA/374 [410] St/374 [410] (NVCL) [384] N S S N N 255 [411] O S S N CN 256* MA [411] (St) [411] AA-b-NIPAM [412] 257 [283] S S N 258 [413] S S N O O St [413] (MA) [413] A See footnote A of Table 3. B See footnote B of Table 3.…”
Section: Hnmentioning
confidence: 99%
See 3 more Smart Citations
“…249 [408] MA [405] St [407] St [408] 250* [405] S S N N N S S 251 [404] MA [405] St [407,409] MA [405] St [404] 252* N N N S S 253 [283] S S N N St [409] 374 [410] MA/374 [410] St/374 [410] (NVCL) [384] N S S N N 255 [411] O S S N CN 256* MA [411] (St) [411] AA-b-NIPAM [412] 257 [283] S S N 258 [413] S S N O O St [413] (MA) [413] A See footnote A of Table 3. B See footnote B of Table 3.…”
Section: Hnmentioning
confidence: 99%
“…[117,130,479] This methodology has been applied to the synthesis of three-armed stars by an in-situ thiol-ene reaction with a triacrylate [130] and has been applied to directly make biopolymer conjugates. [479] A recent study shows that dithioester and trithiocarbonate RAFT agents [R-SC(S)Z] undergo a radical-catalyzed reaction with thiols that results in oxidation of the thiol to a disulfide and concomitant reduction of the RAFT agent to R-H. [481] The relative rates of reaction suggested that dithioester RAFT agents [204] PEGA Ph (58) Butylamine Used in thiol-ene [204] NIPAM SCH 2 CH(CH 3 ) 2 (188) Butylamine/TCEP/HEA butylamine/TCEP/BA One-pot thiol-ene [373] NIPAM SCH 2 CH(CH 3 ) 2 (188) Butylamine/TCEP Used in thiol-ene [371,372] NIPAM Ph (25) LiB(C 2 H 5 ) 3 H Used in thiol-ene [151] NIPAM S(CH 2 ) 2 CO 2 H (170) NaBH 4 Used in thiol-ene [355] NIPAM SC 4 H 9 (166) NaOH/MeOH/EDTA Used in thiol-ene [412] NIPAM Ph (24) Octylamine/DMPP/AMA One-pot thiol-ene [132] NIPAM Ph (24) Octylamine/DMPP/PMA One-pot thiol-ene [132] DEAM Ph (24) Hexylamine/DMPP/MA One-pot thiol-ene [130] St Ph (24) Propylamine/PBu 3 /MA NaBH 4 /PBu 3 /MA One-pot thiol-ene [117] St Ph (24) Propylamine NaBH 4 [205] MMA Ph (82) Hexylamine Conditions to favour disulfide formation [196] MMA Ph (22) Propylamine One-pot methanethiosulfonate [480] NVP OC 2 H 5 (228) NaBH 4 Used in peptide/nucleotide conjugation [396] A Monomer unit adjacent to thiocarbonylthio group. B TCEP -tris(2-carboxyethyl) phosphine hydrochloride, EDTA -ethylenediaminetetraacetic acid, TCEP -tris(2-carboxyethyl phosphine), DMPPdimethylphenylphosphine.…”
Section: Aminolysis/hydrolysis/ionic Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In RAFT polymerizations, a chain transfer agent with the general structure ZC(=S) SR, where Z is an activating group and R is a transferred chemical group, is used to control the chain growth. The thio-carbonyl-thio terminal group present at the final polymer chains can be easily converted to a thiol group for posterior chemical modifications of the polymer material [25,29] . For instance, thiol groups can be used for bioconjugation and development of biomedical applications [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%